Christian ethics and AIDS in Africa today: Exploring the limits of a culture of suspicion and despair - Katongole, Emmanuel M. (Missionalia: Southern African Journal of Mission Studies, 2001)
Discussion of the AIDS epidemic in the light of Christian ethics seems to have got bogged down in narrow moralistic prescriptions, for example over whether or not it is right to use condoms to prevent AIDS. What is often ignores is that the AIDS epidemic is changing the kind of people we are. It has reinforced both Western stereotypes of Africa, and African suspicion of the West, and of the West's intentions in Africa.
Free